Predictive Factors for the Development of Dyspnea Within 7 Days After Admission Among Terminally Ill Cancer Patients. (April 2022) - Matsunuma, Ryo; Yamaguchi, Takashi; Mori, Masanori; Ikari, Tomoo; Suzuki, Kozue; Matsuda, Yoshinobu; Matsumoto, Yoshihisa; Watanabe, Hiroaki; Amano, Koji; Kamura, Rena; Kizawa, Yoshiyuki
Background: Predictive factors for the development of dyspnea have not been reported among terminally ill cancer patients. Objective: This current study aimed to identify the predictive factors attributed to the development of dyspnea within 7 days after admission among patients with cancer. Methods: This was a secondary analysis of a multicenter prospective observational study on the dying process among patients admitted in inpatient hospices/palliative care units. Patients were divided into 2 groups: those who developed dyspnea (development group) and those who did not (non-development group). To determine independent predictive factors, univariate and multivariate analyses using the logistic regression model were performed. Results: From January 2017 to December 2017, 1159 patients were included in this analysis. Univariate analysis showed that male participants, those with primary lung cancer, ascites, and Karnofsky Performance Status score (KPS) of ≤40, smokers, and benzodiazepine users were significantly higher in the development group. Multivariate analysis revealed that primary lung cancer (odds ratio [OR]: 2.80, 95% confidence interval [95% CI]: 1.47-5.31; p = 0.002), KPS score (≤40) (OR: 1.84, 95% CI: 1.02-3.31; p = 0.044), and presence of ascites (OR: 2.34, 95% CI: 1.36-4.02; p = 0.002) were independent predictive factors for the development of dyspnea. Conclusions: Lung cancer, poor performance status, and ascites may be predictive factors for the development of dyspnea among terminally ill cancer patients. However, further studies should be performed to validate these findings.